Efektivitas Pelayanan Perizinan Online Melalui Sistem Izin Investasi Mudah Dan Terpadu (SI IMUT) Di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Semarang - Hammam Mahdy; Augustin Rina Herawati; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Licensing services are a type of service that is principally the responsibility of the government and is carried out with the aim of meeting community needs and following relevant legal regulations, with service products in the form of permits. Semarang City DPMPTSP released an Easy and Integrated Investment Permit System (SI IMUT) to simplify and speed up the licensing process submitted by the public. However, in practice, online licensing through SI IMUT is still not optimal because there are still many complaints about the online licensing system. This study aims to analyze the effectiveness of online licensing services through SI IMUT and the supporting and inhibiting factors for effectiveness. The research method used is descriptive qualitative with data collection techniques of interviews, observation and documentation. This study uses the theory of effectiveness according to Duncan, namely goal attainment, integration, and adaptation, and uses the theory of factors that influence effectiveness according to Najidah, namely coordination, planning, and accuracy of service. The results of the study show that the effectiveness of online licensing services through SI IMUT has not run optimally, this is because the Semarang City DPMPTSP has not carried out socialization as a whole, so that the social process indicators are still not optimal. In addition to the service accuracy factor, people's understanding of online licensing services through SI IMUT is considered to be lacking so that it affects the effectiveness of online licensing services through SI IMUT at DPMPTSP Semarang City